OD „KOREANY” DO „ALMA E CORACAO”. SEMANTYKA I PRAGMATYKA PIOSENEK OLIMPIJSKICH - Nowak, Paweł (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In public space there is a variety of means to express the feeling of belonging to the Olympic community united by the ideas of Baron Pierre de Coubertin. The Olympic torch, five Olympic circles and the Olympic flag all represent this, so do many graphic, verbal and sound signs present in the symbolic public space. One of such messages uniting ‘the Olympians’ would be music, Olympic songs and the Olympic anthem. The several dozens of songs associated with the Olympic games throughout last 30 years are based on the semantics of emotion and the interpretation of spirit, flame, dream which, depending on the author, are more or less clichéd. They are not overly substantial in semantic and pragmatic aspect, but they do activate different contexts and interpretational frames; they are also vague in terms of the theme (it is often unclear whether they are about sports or love). Surely the communication in them is not direct and cooperation is based on presuppositions and implications.